"Wynken de Worde" - Holbrook, Sue Ellen (1995)
Keywords: dept.eng; faculty_collection; sabbatical_report

Topics in Poetry - Shipley, Vivian (Southern Connecticut State University?, 1995)
Keywords: Connecticut; New Haven; Southern Connecticut State University; College students' writings; American; dept.eng; faculty_collection

En Travesti: Women, Gender Subversion, Opera - Blackmer, Corinne E.; Smith, Patricia Juliana (Columbia University Press, 1995)
Keywords: Women in opera; Lesbianism; dept.eng; faculty_collection

The Woman Detective: Gender & Genre - Klein, Kathleen Gregory (University of Illinois Press, 1995)
Kathleen Gregory Klein traces female paid, professional private investigators in British, Canadian, and American novels, revealing that the detective novel is both a reflection of and potential barrier to social change for women. This edition adds sixty new female private eyes to the roster and includes an afterword that assesses the current state of the genre's new and old novels. A comprehensive bibliography and a character list update the field through mid-1994.–(Source of description unspecified.)
Keywords: Detective and mystery stories; English; English-speaking countries; History and criticism; Detective and mystery stories; American; History and criticism; Popular literature; History and criticism; Women detectives in literature; Women in literature; dept.eng; faculty_collection

Women Times Three: Writers, Detectives, Readers - Klein, Kathleen Gregory (Bowling Green State University Popular Press, 1995)
This volume explores the range of relationships among women writers, women detectives and women-centered mystery fiction, and women readers. Focusing on writers as diverse as Sara Paretsky, Joan Hess, Sarah Caudwell, P.D. James, Katherine V. Forrest, Mary Roberts Rinehart, Sue Grafton, D.R. Meredith, Dorothy L. Sayers, and Barbara Wilson, the authors analyze the development of detective fiction with a different agenda: the woman-authored woman detective. Examined through the eyes of actual and hypothetical women readers of the genre, these eleven essays concentrate new attention on the trio of reader, writer, and text when all three are modified by the terms "woman" and "mystery." The first essay collection to propose this gender and genre specific analysis, Women Times Three offers its readers a careful theoretical and critical investigation of both historical and contemporary models of consistently "new" mystery fiction., The essays' authors are not only widely published scholar-critics of mystery/detective fiction but also dedicated fans of the genre. Familiar with the full scope of mystery fiction, they bring insight and enthusiasm to their writing.
Keywords: 20th century; Women; Books and reading; Detective and mystery stories; American; English-speaking countries; English-speaking countries; Authors and readers; English-speaking countries; Feminism and literature; History; History and criticism; American fiction; History and criticism; Detective and mystery stories; English; History and criticism; English fiction; History and criticism; Women detectives in literature; Women and literature; Women authors; dept.eng; faculty_collection

Igbo - Ogbaa, Kalu (Rosen Pub. Group, 1995)
SCSU Faculty Scholar Award
Keywords: Igbo (African people); Juvenile literature; award_winner; dept.eng; faculty_collection

How to Publish and Win Writing Contests - Shipley, Vivian (Southern Connecticut State University?, 1995)
Keywords: Connecticut; New Haven; Southern Connecticut State University; College students' writings; American; dept.eng; faculty_collection

For Martin Luther King - Fort, Charles (Letters to America: Contemporary American Poetry on Race, 1995)
A collection of poems that explore the issues surrounding race relations in American society, told from the experience of Black, Native American, Asian, Arabic, Hispanic, and white cultures.–(Source of description unspecified.)
Keywords: 20th century; African Americans; American poetry; Poetry; Poetry; Race relations; Poetry; Racism; Poetry; United States; Race relations; dept.eng; faculty_collection

Contentious intimations: John Donne, Richard III, and the transgressive structures of seduction - Larocco, S. (Exemplaria, 1995)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

1920 - fighting forces, writing women - Neverow, Vara (English Literature in Transition 1880-1920, 1995)
Citation Key Alias: lens.org/022-699-038-253-776 tex.type: [object Object]
Keywords: dept.eng; ⛔ No DOI found